MOBILE BANKING AS A DIGITAL MARKETING CHANNEL: ROLE IN CUSTOMER ENGAGEMENT AND PRODUCT ACQUISITION IN INDONESIAN SOE KBMI 4 BANKS - Venessa Hardi (CV. Radja Publika, 2026)
The increasing adoption of mobile banking has also changed the interaction of customers with financial institutions in Indonesia. The effect of marketing elements on product acquisition is still uncertain. This study is an analysis of the relationship between the variables of perceived usefulness, perceived ease of use, trust, customer engagement and product acquisition in the use of mobile banking at KBMI 4 Banks in Indonesia namely Bank Mandiri, Bank Negara Indonesia, and Bank Rakyat Indonesia, using the Technology Acceptance Model (TAM) and Customer Engagement Theory. A quantitative approach was adopted and hypotheses were tested by means of a survey of 200 active mobile banking users analyzed by using partial least squares structural equation modeling (PLS-SEM). The PLS-SEM was carried out using SmartPLS 4. The results indicate that mobile banking engagement has an indirect effect to product acquisition, with perceived usefulness and trust as significant mediators between engagement and acquisition behavior. Perceived ease of use, on the other hand, does not play a significant part in this process, pointing to the fact that the ease of use of the interface has become a standard expectation, and not a key consideration when deciding upon purchasing. The TAM model is expanded to capture the idea of digital banking innovation, optimizing mobile banking as an effective channel for product acquisition.